PENYANGKALAN ADANYA TUHAN DALAM PANDANGAN ATEIS DAN SAINS MODERN - Herwansyah Herwansyah (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2017)
The philosophy of the 19th and 20th centuries gave birth to the idea of atheism. Modern atheist figures include Ludwig Feuerbach, Karl Marx, Friedrich Nietzsche, Sigmund Freud and Jean-Paul Sartre. The denial of God presented by each of the 19th and 20th century figures has his own arguments and context. According to Feurbach God is the creation of human delusion. Karl Marx, religion is the opium of the people. Nietzsche, God is dead. Sigmund Freud, religion according to his psychological nature is an illusion. Sartre, the existence of God is nothingness. The denial of God by modern scientists does not mean not to believe in the existence of God at all, but they just have put aside the existence of God. The scientists deny the existence of God with mean to awaken, awaken the religious human beings of the social condition